2009
DOI: 10.1007/s11356-009-0235-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of the natural antibiotic, cinnamic acid, with layered double hydroxides (LDH) as green pesticide

Abstract: This study suggests one of the sound strategies to make a breakthrough in the formulation of green pesticides. Hybridization with inorganic matrixes not only enables the natural antibiotic substances to replace the synthetic ingredients but also adjuvants to be excluded from the formulations. Furthermore, the resulting hybrid exhibits a controlled release of the intercalated substances. Although substantiated further, this study is expected to attract a great deal of attention to reliable application of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This property of the elements is exploited by 10 incorporating them in different kind of materials like fibers, [1] 11 ceramics [2] and coatings [3] etc. But the effectiveness of the 12 antibacterial property lies in the homogenization and well 13 dispersibility of the metals [4]. The dispersibilities of the metals 14 and their ions are at ease in coprecipitation system for synthesizing 15 a ceramic material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This property of the elements is exploited by 10 incorporating them in different kind of materials like fibers, [1] 11 ceramics [2] and coatings [3] etc. But the effectiveness of the 12 antibacterial property lies in the homogenization and well 13 dispersibility of the metals [4]. The dispersibilities of the metals 14 and their ions are at ease in coprecipitation system for synthesizing 15 a ceramic material.…”
mentioning
confidence: 99%
“…(LDH) and benzoate derivatives [12], green pesticides with layered 28 double hydroxide (LDH) hybridized with cinnamic acid [13] and 29 antibacterial drug carrier [14].…”
mentioning
confidence: 99%
“…A third unidentified antifungal compound was detected in both media at a later growth stage. Recently, Park et al [32] reported that cinnamic acid has antifungal activity against the growth of Phytophthora capsici in a PDA medium, and that the acid was very effective for controlling root rot in red pepper.…”
Section: Discussionmentioning
confidence: 99%
“…The hybridisation of natural antibiotic substances with layered double hydroxides could be an alternative for green formulation of pesticides. 88 Humic substances constitute a major fraction of organic matter in natural water and effluents from lakes and rivers. Their presence has been a problem in the water industry and in environmental purification such as soil remediation.…”
Section: Environmental Applicationsmentioning
confidence: 99%